Pemberdayaan Partisipasi Masyarakat dalam Membangun Nilai-Nilai Religius di Desa Wringin Kecamatan Wringin Kabupaten Bondowoso - Muhammad Ulum (GUYUB: Journal of Community Engagement, 2020)
Wringin in Bondowoso District is a rural area in which the most of inhabitants are religious, but there are lots of them having deviant behaviors, such as gambling, illegal lottery, and mony laundry. It seems more difficult since he level of social participation in religious teaching is relatively low. Furthermore, the social empowerment is important in terms of religious teaching regularly undertaken in Mosque of Baitus Mukhlisin Islamic Boardingschool. This program is possibly to increase their religious understanding of daily life aspects, such as social moral values, classification of obligatory and meritorious worships, correct praying procedures, right and duty between married couple, religious parenting, etc.Keywords: Wringin Village, Social Participation, Religious Values